Uma análise do design em tempos de hipermodernismo: do contexto político às dimensões cognitivas e comunicativas - Arruda, Marina Silveira (2013)
The theme of this dissertation is the design of products and environments in hypermodernism times (LIPOVETSKY, 2004). In this context, the design affirms itself, at first sight, as a symptom of the consumer market which function is to elaborate goods to be commercialized, aiming the constant growth of the profits. However, especially in the last decade, the design has been also considered an apparatus even more able to implement ways of life and subjectivities. The goal of this research is to recognize it in this procedural nature, as a systemic thought expressed by the language that engenders it. The main hypothesis is that the body-media notions (KATZ & GREINER, 2005, 2010) together with the distended mind ones (CLARK, 2011) can redefine the design to beyond the objects functionality and commercialization, explaining the dynamic and singular relations among bodies and environments, in each time that a new product is designed and used. In methodological terms, it is a bibliographic research that punctuates and problematizes some aspects of the history and different conceptions of design, approaching it of bibliographies focused on the study of perception (FERRARA, 2001; REINERT, 2012), of discussions about the immaterial labor (NEGRI & LAZZARATO, 2001) and of the sensitive communication that produces subjectivity (SODRÉ, 2006). As research s corpus, will be exemplified situations related to the interior designer s practice and the ways as its practice are represented by the specialized publications. The expected result is the preliminary presentation of a discussion which invigorates the conceptual debate of the procedural nature of the contemporaneous design, vitalizing at the same time its practice